Continued Sensitivity of Plasmodium falciparum to Artemisinin in Guyana, With Absence of Kelch Propeller Domain Mutant Alleles. (30th August 2016) - Rahman, Reyaud; Martin, Maria Jesus Sanchez; Persaud, Shamdeo; Ceron, Nicolas; Kellman, Dwayne; Musset, Lise; Carter, Keith H.; Ringwald, Pascal
Abstract: Because of concerns about possible emergence of artemisinin resistance strains of Plasmodium falciparum in mining areas of the interior of Guyana, a 7-day artesunate trial was conducted from March to December 2014. The day-3 parasite clearance rate, the efficacy of artesunate at day 28, and polymorphism of Kelch 13 ( PfK13 )—the marker of artemisinin resistance—were assessed. The study confirmed the continued sensitivity of P falciparum to artemisinin. A 7-day course of artesunate was 100% efficacious with only 2% (95% confidence interval, .1%–10.9%) of enrolled subjects positive at day 3. All day-0 parasite samples were wild type. Continued resistance monitoring is nevertheless recommended, given the widespread availability and uncontrolled use of artemisinin drugs in mining areas of Guyana.